Observing the simulation behaviour of Magnesium alloy metal sandwich panel under cyclic loadings (Fracture and Structural Integrity, 2022)
This study aims to investigate the delamination effect of a metal sandwich panel using a four-point bending simulation under continual spectrum loading. The most recent core designs of the sandwich panel have a cavity that can increase vulnerability in terms of bonding strength under constant cyclic loading. The sandwich panel is simulated under constant cyclic loading using different core design configurations, which are rounded dimple, hemispherical dimple, and smooth surface core design. There are two types of conditions used; no pre-stress and pre-stress loads with variable stress ratios based on Gerber stress life theory. Results showed that dimple core design enhanced mechanical behaviour and fatigue life performance about 33% and 5%, respectively, compared to the sandwich panel with a smooth surface core design. It is highlighted that modification on the surface of core design could be beneficial to enhance the bonding strength performance of sandwich panels and prevent early delamination under extreme conditions such as constant cyclic loading. This study is beneficial to enhance the bonding strength for sandwich panels against extreme conditions such as high impact load and continuous cyclic load.
Keywords: Computational analysis; Cyclic loading; Fatigue life; Magnesium alloy; Sandwich panel